Impact of copper nanoparticles on tribofilm formation determined by pin-on-disc tests with powder supply: Addition of artificial third body consisting of Fe3O4, Cu and graphite. (June 2017) - Rodrigues, A.C.P.; Österle, W.; Gradt, T.; Azevedo, C.R.F.
Abstract: Copper, magnetite and graphite particles were mixed in order to observe their impact on the coefficient of friction (CoF) during pin-on-disc tests and on the tribofilm formation after testing. Pure magnetite powder provided a value of CoF of 0.4. Magnetite-copper mixtures tested at 400 °C revealed lower CoF values ( 0.4) than those at room temperature ( 0.6). Magnetite-graphite and magnetite-graphite-copper mixtures presented lower CoF values ( 0.3). All systems formed a magnetite-based tribofilm and patches of metallic copper were found on the tribosurfaces of the mixtures containing copper. Carbon layers and graphite nanoinclusions were observed in the graphite mixtures. The incorporation of zirconia particles, a by-product of ball milling mixing, prevented the selective transfer of graphite and copper to the tribosurfaces of some of the samples. Highlights: Mixtures of Cu, Fe3 O4 and graphite particles were added to pin/disc tribotests. The transfer layer was observed with focused ion beam, EDS, XEDS mapping and TEM. Graphite and Cu particles may suffer selective transfer to first bodies' surfaces. Selective transfer may be prevented by adding an abrasive to the third body. Cu- Fe3 O4 mixtures tested at 400 °C presented lower CoF than at room temperature.